Association of Dietary Energy Density with Macronutrient and Fiber Intake among Women with Central Obesity in a Community-Based Group Exercise - Anggun Rusyantia; Endang Sri Wahyuni; Sutrio Sutrio (Media Ilmiah Kesehatan Indonesia, 2026)
Central obesity is a health problem associated with an increased risk of cardiometabolic diseases, particularly among women. One factor that plays a role in weight management and obesity is dietary energy density, defined as the amount of energy contained in each gram of food or beverage consumed. This study aimed to analyze the association between dietary energy density and the intake of macronutrients and fiber among women with central obesity in a fitness community. This study was an observational study with a cross-sectional design involving 30 women aged 19–50 years who were members of the Lampung Workout Community, had a waist circumference of ≥80 cm, and had no history of certain serious diseases. Carbohydrate, protein, fat, and fiber intake was collected using two 24-hour food recalls on one weekday and one weekend day, and then analyzed using NutriSurvey. Dietary energy density was calculated by dividing total energy intake by the total weight of foods and beverages consumed. Bivariate analysis was performed using Pearson’s correlation test with a significance level of p < 0.05. The results showed that most respondents had high dietary energy density, accounting for 63.3%. Carbohydrate, fat, and fiber intake were significantly associated with dietary energy density, whereas protein intake showed no significant association. Fat intake was positively associated with dietary energy density, while fiber intake was negatively associated. These findings indicate that regulating the consumption of low-energy-density, high-fiber, and low-fat foods may serve as a strategy for the prevention and management of central obesity among women.